KOMUNIKASI ORGANISASI PERGERAKAN MAHASISWA ISLAM INDONESIA (PMII) DALAM TINGKAT BERPIKIR KRITIS MAHASISWA DI INSTITUT AGAMA ISLAM SAHID BOGOR - Mardiatama , Welinda (Fakultas Ilmu Dakwah dan Komunikasi, 2022)
This study aims to determine whether PMII's organizational communication has a significant effect on the level of critical thinking of students at the Sahid Islamic Institute, Bogor. This study used a quantitative approach with data collection techniques using a statement questionnaire with 4 alternative answers. The population used in this study were members of the Islamic Student Movement organization with a sampling technique of 22 members of the Indonesian Islamic Student Movement organization. The results of the analysis and discussion show that the tcount is 0.454 < ttable 2.085, which means that PMII's organizational communication has no significant effect on the level of critical thinking of students at the Sahid Islamic Institute, Bogor.